Photocatalytic Hydrogen Generation from Water-Annealed TiO2 Nanotubes with White and Grey Modification - Fu, Fan; Cha, Gi; Wu, Zhenni; Qin, Shanshan; Zhang, Yan; Chen, Yuyue; Schmuki, Patrik (ChemElectroChem, 2021)
In recent years, photocatalytic reactions on anodic TiO2 nanotubes have been intensively investigated. In order to show photocatalytic activity, anodically formed nanotubes need to be crystallized to anatase. This is conventionally done by thermal annealing in air at temperatures 400–600 °C. Recently, a so-called “water annealing” treatment has been reported to be effective to also create a highly active form for photocatalysis. Here we report on the feasibility of using a water annealing treatment of TiO2 nanotubes to create a photocatalyst for H2 production that is as active as conventional thermal annealing. If the water-annealed samples are additionally hydrogenated to a so-called “grey” modification, a further significant improvement of the photocatalytic activity for H2 evolution can be achieved – this without the use of any noble metal co-catalyst. A combination of water annealing, thermal annealing, followed by hydrogenation can deliver a H2 generation activity that is more than five times higher than that achieved by thermal annealing of anodic TiO2 nanotubes.
CRIS-Team Scopus Importer:2021-02-05
Keywords: hydrogenation; optimized water annealing; TiO; titanium (III); water splitting

Self-assembly and activation of a titania-nanotube based photocatalyst for H-2 evolution - Fu, Fan; Wu, Zhenni; Cha, Gi; Schmuki, Patrik (Chemical Communications, 2021)
Constructing an efficient photocatalyst for H-2 production generally requires the integration of several functional features in and on a semiconductor platform. This is conventionally done by a classic step-by-step synthesis. Here, we report the self-assembly of an amorphous titania nanotube based system when illuminated for extended time in suitable aqueous solutions. Over time, not only photodeposition of a co-catalyst can take place, but also in situ crystallization and morphology changes occur that can provide a higher H-2 production than observed for a classically assembled photocatalyst.
CRIS-Team WoS Importer:2021-07-09

Water Annealing of TiO2 Nanotubes for Photocatalysis Revisited - Fu, Fan; Cha, Gi; Denisov, Nikita; Chen, Yuyue; Zhang, Yan; Schmuki, Patrik (ChemElectroChem, 2020)
Over the past years, so-called water annealing of TiO2 nanotube (NT) arrays has attracted considerable attention as a tool to enhance the nanotubes’ photocatalytic properties. The present work investigates the effect of different water-annealing treatments on TiO2 nanotubes and compares it to thermally annealed tubes. We find that the most effective water annealing is water immersion of TiO2 NT arrays at 70 °C for several days. The two main effects are i) a partial crystallization of the tubes to anatase, and ii) an etching of the tube walls that leads to a roughening of the walls and, thus, to a higher surface area. Under the best conditions, water annealing is almost as effective in providing enhanced photocatalytic AO7 degradation as a classic thermal annealing of the tubes. We, however, find that water annealed tubes – due to their only partial crystallization – do not perform well when used as photoelectrodes. For photocatalysis, most efficient is a combination of water annealing, followed by thermal annealing, which provides both a larger surface area and a high crystallinity.
CRIS-Team Scopus Importer:2020-07-24
Keywords: anodization; crystallinity; photocatalytic reaction; TiO; water annealing